Socialization of the Role of Chest X-Rays in Patients in the Radiology Installation of M. Zein Painan Regional Hospital, Pesisir Selatan Regency, West Sumatra - Livia Ade Nansih; Sri Wahyuni; Eggy Putri Asih; M. Fobby Gutama (PT. Anagata Sembagi Education, 2026)
Chest X-ray is a fundamental radiographic examination widely used as a first-line imaging modality for screening, diagnosing, and evaluating thoracic diseases, including tuberculosis (TB), lung disorders, and cardiovascular abnormalities. Despite its routine use, many patients have limited understanding of its purpose, benefits, and examination procedures, which may lead to anxiety and reduced compliance. This community service activity aimed to improve patients’ knowledge regarding chest X-ray examinations at the Radiology Installation of M. Zein Painan Regional Hospital. The program was conducted on December 23, 2024, using individual (one-on-one) educational sessions involving 14 patients awaiting chest X-ray examinations. Educational materials covered the definition, indications, benefits, examination procedures, patient preparation, radiation safety, and the importance of following radiographer instructions. Effectiveness was assessed using a nine-item questionnaire administered before and after the education. Results demonstrated a marked improvement in patient knowledge, with post-test scores reaching 100% correct responses for most items, compared with 36–79% in the pre-test. The greatest improvements were observed in understanding examination procedures and radiation safety, particularly the need to report pregnancy before exposure. These findings indicate that individualized patient education effectively enhances knowledge and supports better compliance during chest X-ray examinations. Although the small sample size and one-group pre–post design limit generalizability, integrating continuous patient education into radiology services is recommended to improve health literacy and service quality.